Pemberdayaan Kelompok Wanita Tani dalam Penerapan Teknologi Porasi Padat Berbasis Mol Nasi Basi dalam Budidaya Kacang Hijau di Pekarangan - Gusniwati Gusniwati; Neliyati Neliyati; Buhaira Buhaira; Made Deviani Duadja; Miranti Sari Fitriani (Universitas Medan Area, 2022)
This service aims to provide guidance, counseling and assistance on the application of MOL Nasi stale, as a local microbe for biodecomposers in processing household waste into solid organic fertilizer (porasi) and as liquid organic fertilizer used for mung bean plants. Methods The implementation of the activity is counseling to all members of the Women Farmers Group followed by a demonstration at the village office and continued with field practice at the women's group home and demonstration of land cultivation plots and planting green beans. The implementation stage is divided into 3 stages, namely the preparation, implementation, and evaluation stages. The preparation stage includes the preparation of tools and materials and leaflets for extension participants and the manufacture of tubs or culverts for the manufacture of Porasi and land preparation for planting green beans in people's yards. The results of the activity show that community participation in the percentage of attendance at the time of counseling is classified as moderate, participating in technological counseling is high, applying technology is classified as moderate, land processing for planting is low to moderate because it is assisted by the family.